Kerapatan dan Distribusi Stomata Daun Spesies Mangrove di Desa Negeri Lama Kota Ambon - Mercyana Marantika; A Hiariej; D E Sahertian (Universitas Hasanuddin, 2021)
This study aims to determine the density and distribution of mangrove species stomata in the Negeri Lama village of Ambon City. Quantitative descriptive methods are used to explain the stomata of mangrove species based on observations of transverse incisions on the undersurface of the leaf using an Olympus type BX51 microscope and Obtiplab type E-330. The results showed that the stomata density of the mangrove species Aegiceras corniculatum, Acanthus ilicifolius, Bruguiera cylindrica, Rhizophora apiculata, and Sonneratia alba in the Old Country Village were categorized as low density. The distribution of stomata in the mangrove species Aegiceras corniculatum, Acanthus ilicifolius, Bruguiera cylindrica, Rhizophora apiculata, and Sonneratia alba in the Old Country Village are classified as scattered with only distribution in the lower epidermis or under the leaf surface.